Migration Infrastructure - Xiang, Biao; Lindquist, Johan (The International migration review, 2014)
Based on the authors’ long‐term field research on low‐skilled labor migration from China and Indonesia, this article establishes that more than ever labor migration is intensively mediated. Migration infrastructure – the systematically interlinked technologies, institutions, and actors that facilitate and condition mobility – serves as a concept to unpack the process of mediation. Migration can be more clearly conceptualized through a focus on infrastructure rather than on state policies, the labor market, or migrant social networks alone. The article also points to a trend of “infrastructural involution,” in which the interplay between different dimensions of migration infrastructure make it self‐perpetuating and self‐serving, and impedes rather than enhances people's migratory capability. This explains why labor migration has become both more accessible and more cumbersome in many parts of Asia since the late 1990s. The notion of migration infrastructure calls for research that is less fixated on migration as behavior or migrants as the primary subject, and more concerned with broader societal transformations.